Observations of Buried Lake Drainage on the Antarctic Ice Sheet. Issue 15 (31st July 2020) - Dunmire, D.; Lenaerts, J. T. M.; Banwell, A. F.; Wever, N.; Shragge, J.; Lhermitte, S.; Drews, R.; Pattyn, F.; Hansen, J. S. S.; Willis, I. C.; Miller, J.; Keenan, E.
Abstract: Between 1992 and 2017, the Antarctic Ice Sheet (AIS) lost ice equivalent to 7.6 ± 3.9 mm of sea level rise. AIS mass loss is mitigated by ice shelves that provide a buttress by regulating ice flow from tributary glaciers. However, ice‐shelf stability is threatened by meltwater ponding, which may initiate, or reactivate preexisting, fractures, currently poorly understood processes. Here, through ground penetrating radar (GPR) analysis over a buried lake in the grounding zone of an East Antarctic ice shelf, we present the first field observations of a lake drainage event in Antarctica via vertical fractures. Concurrent with the lake drainage event, we observe a decrease in surface elevation and an increase in Sentinel‐1 backscatter. Finally, we suggest that fractures that are initiated or reactivated by lake drainage events in a grounding zone will propagate with ice flow onto the ice shelf itself, where they may have implications for its stability. Plain Language Summary: The Antarctic Ice Sheet (AIS) is losing mass, thereby contributing to sea level rise. Ice shelves, which are thick floating layers of glacier ice extending from the glaciers on land, buttress much of the AIS and protect it from even more mass loss. The stability of these ice shelves is threatened by meltwater ponds that form during the summer and may cause ice shelves to break up. Here, we present field observations from Antarctica of a buried meltwater lake drainage via vertical fractures. To detect the drainage event, we use radar observations collected in the field, along with surface height changes and radar images from satellites, from both before and after the drainage event. Our study improves the understanding of meltwater processes on Antarctic ice shelves, and implications of those processes on ice‐shelf stability. Key Points: We present the first field observations of the rapid drainage of a buried lake via hydrofracture in Antarctica Lake‐bed fractures are detected from ground penetrating radar prior to drainage and suggest the lake may have been preconditioned to drain Remote sensing analysis of digital elevation model and Sentinel‐1 microwave image differences provide additional lake evolution information